The Theoretical Description for Psilocin Electrochemical Determination over Cobalt Oxyhydroxide - Volodymyr Tkach; Mykhailo Kucher; Marta Kushnir; Yana Ivanushko; Yüksel Akınay; Necdet Karakoyun; Petro Yagodynets; Zholt Kormosh (Orbital: The Electronic Journal of Chemistry, 2023)
The possibility of psilocin electrochemical determination over cobalt (III) oxyhydroxide-modified anode is evaluated from the mathematical point of view. Psilocin is thereby oxidized yielding either micro- or macromolecular product, being both of them important for the economical and green conducting polymer composite for electrocatalysis, electroanalysis and energy conversion. The analysis of the correspondent mathematical model confirms, that, despite of the high probability of the oscillatory behavior, the electrochemical process is efficient from both analytical and synthetical point of view.